2015
DOI: 10.1007/s12526-015-0366-0
|View full text |Cite
|
Sign up to set email alerts
|

From chemosynthesis-based communities to cold-water corals: Vulnerable deep-sea habitats of the Gulf of Cádiz

Abstract: Your article is protected by copyright and all rights are held exclusively by Senckenberg Gesellschaft für Naturforschung and Springer-Verlag Berlin Heidelberg. This e-offprint is for personal use only and shall not be selfarchived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…We have demonstrated that there is a strong relation between the NACW-MOW interface, associated with the activity of internal waves, and the abundance of benthic suspension feeders. This supports the hypothesis that the biological importance of seamounts in the pathway of the MOW through the eastern Atlantic (WWF, 2004;Oceana, 2005;Rueda et al, 2016) might be associated to internal waves in the NACW-MOW interface, that improves the favorable conditions for benthic suspension feeders to grow on the slope of the seafloor elevations.…”
Section: Summary and Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…We have demonstrated that there is a strong relation between the NACW-MOW interface, associated with the activity of internal waves, and the abundance of benthic suspension feeders. This supports the hypothesis that the biological importance of seamounts in the pathway of the MOW through the eastern Atlantic (WWF, 2004;Oceana, 2005;Rueda et al, 2016) might be associated to internal waves in the NACW-MOW interface, that improves the favorable conditions for benthic suspension feeders to grow on the slope of the seafloor elevations.…”
Section: Summary and Discussionsupporting
confidence: 84%
“…Following the path of the MOW through the eastern Atlantic, three seafloor elevated features, where CWC have been described (WWF, 2004;Oceana, 2005;Rueda et al, 2016), were selected as target regions for this study: the Gazul mud volcano and the Ormonde and Formigas seamounts (Figure 1). Both Gazul and Ormonde are directly in the pathway of the MOW after it outflows through the Strait of Gibraltar, while Formigas, located further away in the middle of the Atlantic, is influenced by the westward branch of the MOW (Bashmachnikov et al, 2015).…”
Section: Area Of Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies noted the presence of deep-sea suspension feeding species previously known only from the Mediterranean (e.g., the sponges Geodia anceps, Coelosphaera cryosi, and Petrosia raphida) at NE Atlantic locations, such as the Gulf of Cadiz (Spain; Palomino et al, 2016;Sitjá et al, 2018). This area is dominated by aggregations of scleractinians and gardens of large gorgonians and black corals (e.g., M. oculata, Acanthogorgia spp., Antipathes dichotoma, Leiopathes glaberrima; Figure 2) with particular locations, such as Gazul mud volcano, representing a biodiversity hotspot with more than 400 associated species (Rueda et al, 2016;Ramalho et al, 2018;Sitjá et al, 2018). The current distribution of living L. pertusa and M. oculata in the canyons of the Bay of Biscay coincides with the lower limit of the boundary between the ENACW and the MOW (De Mol et al, 2011), as does the distribution of carbonate mounds and CWC reefs in the Porcupine Seabight (De Mol et al, 2002, 2005White and Dorschel, 2010) and other contourite systems in the NE Atlantic (Van Rooij et al, 2007a,b;Hernández-Molina et al, 2009).…”
Section: Cold-water Coral Reefs and Gardensmentioning
confidence: 99%
“…CWC development and hydrocarbon-rich seepage are consequently linked via the formation of MDAC deposits, which provide the hard substrata needed for CWC larval settlement (e.g. Díaz-del-Rio et al, 2003;Van Rooij et al, 2011;Magalhães et al, 2012;Le Bris et al, 2016;Rueda et al, 2016). If too severe, however, fluid flow and associated metabolic processes can result in local conditions that are lethal to CWCs (see 4.3).…”
Section: Ecological Meaning Of Hydrocarbon-rich Seepage For Cwcsmentioning
confidence: 99%